Harnessing spatiotemporal data characteristics to facilitate large-scale analytics over voluminous, high-dimensional observational datasets - Rammer, Daniel P., author; Pallickara, Shrideep, advisor; Pallickara, Sangmi Lee, advisor; Ghosh, Sudipto, committee member; Breidt, Jay, committee member (Colorado State University. Libraries, 2021)
Spatiotemporal data volumes have increased exponentially alongside a need to extract knowledge from them. We propose a methodology, encompassing a suite of algorithmic and systems innovations, to accomplish spatiotemporal data analysis at scale. Our methodology partitions and distributes data to reconcile the competing pulls of dispersion and load balancing. The dispersion schemes are informed by designing distributed data structures to organize metadata in support of expressive query evaluations and high-throughput data retrievals. Targeted, sequential disk block accesses and data sketching techniques are leveraged for effective retrievals. We facilitate seamless integration into data processing frameworks and analytical engines by building compliance for the Hadoop Distributed File System. A refinement of our methodology supports memory-residency and dynamic materialization of data (or subsets thereof) as DataFrames, Datasets, and Resilient Distributed Datasets. These refinements are backed by speculative prefetching schemes that manage speed differentials across the data storage hierarchy. We extend the data-centric view of our methodology to orchestration of deep learning workloads while preserving accuracy and ensuring faster completion times. Finally, we assess the suitability of our methodology using diverse high-dimensional datasets, myriad model fitting algorithms (including ensemble methods and deep neural networks), and multiple data processing frameworks such as Hadoop, Spark, TensorFlow, and PyTorch.
Keywords: distributed analytics; spatiotemporal; distributed systems; big data